2022
DOI: 10.3390/children9060781
|View full text |Cite
|
Sign up to set email alerts
|

The Association between ADHD and Celiac Disease in Children

Abstract: Controversy around the association between celiac disease (CeD) and attention deficit hyperactive disorder (ADHD) was addressed by a systematic review in 2015, ultimately showing no association. Since 2015, there have been several studies showing an association between celiac disease and attention deficit hyperactive disorder. This is an updated systematic review. Background: Most experts agree on the recommendation to not screen as part of the standard of care for ADHD in persons with CeD or vice versa. Simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…A review by Sonia Gaur suggested that it is better to evaluate the association between ADHD and celiac disease on the basis of different sub-types of ADHD, specifically in the inattentive type [ 24 ]. Another pre vious study by Efe et al ., reported an improvement in inattentive behavior among ADHD patients who received a GFD [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review by Sonia Gaur suggested that it is better to evaluate the association between ADHD and celiac disease on the basis of different sub-types of ADHD, specifically in the inattentive type [ 24 ]. Another pre vious study by Efe et al ., reported an improvement in inattentive behavior among ADHD patients who received a GFD [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, more than 85% of patients diagnosed with migraine display DAO deficiency [ 30 ]. Moreover, ADHD is closely associated with celiac disease [ 133 ] and other food allergies that might be the counterpart of what Speer coined as “gastrointestinal allergy” within SATFS. Indeed, Tryphonas and Trites (1979) reported that 47% of the 90 hyperactive children referred were allergic to at least one food [ 134 ].…”
Section: Speer Allergic Tension-fatigue Syndrome (Satfs) Re-visitedmentioning
confidence: 99%
“…A case of CD that is left untreated increases the likelihood of having symptoms that are comparable to those of ADHD. Due to the presence of ADHD-like cognitive and behavioral features in untreated CD, doctors should be aware of the possibility of elements of ADHD [59].…”
Section: Attention Deficit Hyperactivity Disorder (Adhd)mentioning
confidence: 99%